Manajemen Kepemimpinan Kepala Sekolah di SMP PGRI Pangolombian - Fecky Evendy Singal (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2025)
This study discusses the principal’s leadership management at SMP PGRI Pangolombian. The research focuses on the principal’s understanding of leadership management, its implementation, and efforts to improve it. This study employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings show that the principal understands the importance of leadership management, but its implementation has not been optimal, particularly in planning, control, and decision-making. The principal has attempted to improve leadership through task distribution, communication, approaches to school members, and collaboration with related stakeholders.